Determinants of trust in healthcare facilities among community-based health insurance members in the Manna district of Ethiopia - Wakuma Akafu; Teferi Daba; Edosa Tesfaye; Firanbon Teshome; Tesfaye Akafu (BMC, 2023)
Abstract Background Low-income countries, including Ethiopia, face substantial challenges in financing healthcare services to achieve universal health coverage. Consequently, millions of people suffer and die from health-related conditions. These can be efficiently managed in areas where community-based health insurance (CBHI) is properly implemented and communities have strong trust in healthcare facilities. However, the determinants of community trust in healthcare facilities have been under-researched in Ethiopia. Objective To assess the determinants of trust in healthcare facilities among community-based health insurance members in the Manna District of Ethiopia. Methods A community-based cross-sectional study was conducted from March 01 to 30, 2020 among 634 household heads. A multistage sampling technique was used to recruit the study participants. A structured interviewer-administered questionnaire was used to collect the data. Descriptive statistics were computed as necessary. Multivariable linear regression analyses were performed, and variables with a p-value < 0.05 were considered to have a significant association with households' trust in healthcare facilities. Results In total, 617 households were included in the study, with a response rate of 97.0%. Household age (ß=0.01, 95% CI:0.001, 0.0013), satisfaction with past health services (ß=0.13, 95% CI:0.05, 0.22), perceived quality of services (ß= -0.47, 95% CI: -0.64, -0.29), perceived provider's attitude towards CBHI members (ß = -0.68, 95% CI: -0.88, -0.49), and waiting time (ß= -0.002, 95% CI:- 0.003, -0.001) were determinants of trust in healthcare facilities. Conclusion This study showed that respondents' satisfaction with past experiences, older household age, long waiting time, perceived poor quality of services, and perceived unfavorable attitudes of providers towards CBHI members were found to be determinants of trust in healthcare facilities. Thus, there is a need to improve the quality of health services, care providers' attitudes, and clients' satisfaction by reducing waiting time in order to increase clients' trust in healthcare facilities.